British idealism a history - Mander, W. J. (Oxford : Oxford University Press, 2011)
W.J. Mander presents the first ever synoptic history of British idealism, the school of thought which dominated English-language philosophy from the 1860s to the early 20th century. He restores to its proper place this period of philosophy, introduces the exponents of idealism and explains its concepts and doctrines.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Idealism, English -- History